PENGARUH KINERJA KEUANGAN DAERAH PADA ALOKASI BELANJA MODAL KABUPATEN DAN KOTA DI PROVINSI BALI - Martini, Kadek; Dwirandra, A.A. N.B. (E-Jurnal Akuntansi; Vol 10 No 2 (2015), 2015)
Financial performance is not directly proportional to the area allegedly on capital expenditure, while capital expenditure has the ability to accelerate the region's economy. It is seen from the empirical research and data that says absolute proportion of capital expenditure below 25 percent nationally. The purpose of this study was to determine the effect on the financial performance of the capital expenditure. The results showed that the financial performance consisting of the dependency ratio and a significant negative effect on capital expenditure, revenue effectiveness ratio is positive but not significant effect on the allocation of capital expenditures, financing SiLPA rate ratios and significant negative effect on the allocation of capital expenditures, fiscal space ratio effect positive and significant in the allocation of capital expenditure, the efficiency ratio and a significant negative effect on capital expenditure, and the ratio of contribution of public enterprises is positive but not significant effect on capital expenditure.
Keywords: Financial Performance, Capital Expenditure